TSO-DSO coordination in the joint balancing and flexibility markets considering classification and participation of VPPs - Cai, Qinqin; Xu, Ying; Yi, Zhongkai; Tu, Zhenghong (Energy (Oxford), 2025)
Virtual power plants (VPPs) have emerged as crucial market participants, playing a pivotal role in maintaining power system balance through the provision of flexibility services. However, the participation of VPPs in the market raises potential conflicts between the transmission system operator (TSO) and the distribution system operators (DSOs). To address this issue, this paper proposes a hierarchical coordination architecture of TSO-DSO with bidirectional product demands and price information exchange for joint balancing and flexibility markets. Within the architecture, a distributionally robust chance-constrained (DRCC) approach is established to address system uncertainties. Furthermore, a classification approach based on the Canopy and K-medoids clustering algorithms is developed to establish well-defined market participation rules for distributed flexibility resources. The algorithm facilitates resource management and regulation by enabling the transmission-level virtual power plants (TVPPs) to participate in the wholesale market and the distribution-level virtual power plants (DVPPs) to participate in the local market. Case studies demonstrate that active coordination and effective classification are essential for improving the efficiency and economic performance of the joint market, particularly facilitating the coordinated utilization of distributed flexibility resources between the wholesale market and the local markets. •A hierarchical coordination architecture for two-level markets is proposed.•The centralized market is decomposed into a TSO and multiple DSO subproblem.•The TVPP and DVPP are clustered based on the Canopy and K-medoids algorithm.•The bidirectional price information is exchanged based on the TLMP and DLMP.•The uncertainty is addressed by enhancing the flexibility using the DRCC algorithm.